Structure of the Channels in the Outer Mitochondrial Membrane: Electron Microscopic Studies of the Periodic Arrays Induced by Phospholipase a(2) Treatment of the Neurospora membrane - Mannella, C. A. (1986)
The channel proteins in outer membranes of Neurospora crassa mitochondria spontaneously organize into periodic arrays when the membranes are dialyzed in the presence of soluble phospholipase A(2). Electron microscopic images have been recorded at different electron doses from channel arrays in a variety of negative stains, as well as in vitreous ice. Fourier or correlation averages are formed from image fields containing a few hundred unit cells. These averages can be subsequently classified by correspondence analysis and summed to form representative averages over thousands of unit cells. In averages of negatively stained arrays, the stain-filled channel openings are bounded by smaller stain-excluding maxima. The projections of the channel openings are smaller and the subsidiary maxima are more pronounced for channel arrays contrasted with dilute (0.1%) uranyl acetate or aurothioglucose than for arrays embedded in 1% uranyl acetate. Projection images of unstained, ice-embedded membranes provide direct information about distribution of protein and lipid in the VDAC arrays. First experiments have yielded density maps with an apparent Fourier resolution of ∼1/(2 nm).